Efek Analgetik Ekstrak Etanol Daun Tampa Badak (Voacanga foetida (Bl.) K. Schum) Pada Mencit Putih Jantan - Adriani Susanty; Armon Fernando; Ivona Adelin (Fakultas Farmasi Universitas Andalas, 2014)
A study on the analgesic activity ethanolic extract of Voacanga foetida leaves has been conducted on male mice by using Writhing test. The mice were induced with 0.1 mL of glacial acetic acid 1%. The extract was administered orally in the doses of 250, 500, and 1000 mg/kg, suspended with NaCMC 1%, while 65 mg/kg acetosal was used as positive control. The data was analyzed with two way ANOVA. The study revealed that the extract exhibited analgesic effect insignificantly different with acetosal at the doses of 250, 500, and 1000 mg/kg. This effect was different with negative control (p<0.05).